SAE Technical Paper Series 2018
DOI: 10.4271/2018-01-0890
|View full text |Cite
|
Sign up to set email alerts
|

Double Compression Expansion Engine: A Parametric Study on a High-Efficiency Engine Concept

Abstract: The Double compression expansion engine (DCEE) concept has exhibited a potential for achieving high brake thermal efficiencies (BTE). The effect of different engine components on system efficiency was evaluated in this work using GT Power simulations. A parametric study on piston insulation, convection heat transfer multiplier, expander head insulation, insulation of connecting pipes, ports and tanks, and the expander intake valve lift profiles was conducted to understand the critical parameters that affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The intake air temperature was fixed at 60°C while two different intake air pressure (absolute) of 1.7 and 2.3 bar was used. The intake temperature and pressure were increased to match the TDC temperature and pressure of the previous study [26]. Both the coolant and oil temperature were maintained at 85°C.…”
Section: Engine Operating Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intake air temperature was fixed at 60°C while two different intake air pressure (absolute) of 1.7 and 2.3 bar was used. The intake temperature and pressure were increased to match the TDC temperature and pressure of the previous study [26]. Both the coolant and oil temperature were maintained at 85°C.…”
Section: Engine Operating Conditionsmentioning
confidence: 99%
“…Among these combustion technologies, DCEE concept started attracting attention lately. Previous simulation studies [22,[24][25][26][27] suggested that this concept can accomplish a high BTE of 56% at air-fuel ratio of 3.0. In this proposed concept, a lowpressure (LP) and a high-pressure (HP) cylinders.…”
Section: Introductionmentioning
confidence: 99%
“…Using the DCEE concept, Lam et al demonstrated brake efficiencies of 56 % [8] as well as 52.7 % [9]. Further efficiency improvements have then been achieved by Shankar et al [10] with the use of insulation to reduce heat losses. This study proves the importance of heat transfer reductions for this concept.…”
Section: /15/2019mentioning
confidence: 99%
“…Based on this concept, Lam et al [3,4] reported up to 52.7 % brake thermal efficiency for different engine operating conditions. Further efficiency improvement has been demonstrated for the DCEE concept by Shankar et al [5] with the use of insulation to reduce the heat transfer losses.…”
Section: Introductionmentioning
confidence: 99%